The Role of Social Networking Sites (SNS) and mHealth Pregnancy Apps in Maternal Health Literacy and Behavior - Renee L. Buster; Thomas Guffey; Supriya Rana (American Journal of Health Promotion, 2026)
Purpose To examine the relationship between social networking service (SNS) usage and maternal health literacy (MHL) among women in the U.S., and to assess pregnancy app use. Design Cross-sectional survey study. Setting Qualtrics data collection from U.S. women aged 18-49 who were currently or previously pregnant. Sample A total of 244 participants met the inclusion criteria. Measures Maternal health literacy was assessed using a modified Maternal Health Literacy Inventory in Pregnancy (MHELIP) scale covering decision-making, knowledge, assessment of information, and information seeking. SNS usage was measured via the SNS Usage & Needs Scale (SNSUN). Additional items assessed pregnancy app use and preferred online sources. Analysis Multiple linear regression models evaluated the associations between SNS usage and MHL subdomains, controlling for age. Dummy variables were created to compare exclusive SNS users, combined SNS and other online resource users, and non-users. Results SNS use significantly predicted higher overall perceived MHL (B = 5.61, P < .001), particularly in perceived knowledge (B = 7.00, P < .001), information assessment (B = 7.45, P < .001), and information seeking (B = 6.49, P < .001). However, exclusive SNS reliance was linked to lower overall perceived MHL (B = −4.96, P = .023) and perceived knowledge scores (B = −8.90, P = .002). Seventy-four percent reported using pregnancy apps; 63.1% expressed a need for better app quality. Conclusion While SNS usage correlates with improved perceived MHL, reliance solely on SNS may be insufficient.